How schools affect neighbourhoods: a conceptual framework for the multiple roles of public schools - Oskar Rönnberg; Venla Bernelius; Isabel Ramos Lobato (Taylor & Francis Group, 2024)
Schools are often seen primarily as places of education and learning. However, in addition to providing pupils with knowledge and skills needed in life, schools have a central role in forming and structuring life in their neighbourhoods. In this paper, we propose a conceptual framework for understanding the role and potential of schools in neighbourhood and social development. We illustrate the conceptual framework with empirical data from a survey among residents in five Finnish cities, where the link between schools and neighbourhoods is traditionally strong as school admission is based on catchment areas. We argue for a broader perspective on schools by paying attention to the three significant roles of schools: their educational role, their role in structuring residential decisions and social composition of neighbourhoods, and thirdly, their role as a hub for services and social life.